Seronegative occult hepatitis C infection among hemodialysis patients: A prevalence study. Issue 2 (11th August 2020) - Mahmoudvand, Shahab; Shokri, Somayeh; Azaran, Azarakhsh; Seyedian, Seyed S.; Makvandi, Manoochehr; Mirzaei, Habibollah; Sheikhrobat, Sheida B.
Abstract: The aim of this study was to investigate the prevalence of occult hepatitis C virus (HCV) infection (OCI) among HD patients. Blood samples were taken from 79 HD patients and their sera were evaluated for the presence of anti‐HCV. Both the sera and peripheral blood mononuclear cells (PBMCs) were then checked for HCV RNA by nested reverse transcriptase‐polymerase chain reaction. Anti‐HCV was positive among 4/79 (5.1%) of the patients. From 75 patients who were negative for anti‐HCV, 71 (94.7%) patients were also negative for HCV RNA in sera samples but five of them were positive for HCV RNA in PBMCs. Totally, out of 79 patients, HCV RNA was detected in PBMCs of five (6.3%) patients, indicating that these patients had OCI. No significant difference was observed between the frequency of OCI and gender ( P ‐value = .6). HCV genotype in all five cases of OCI was genotype 3a. Our study showed prevalence rate of 6.3% OCI infection in HD patients. Regarding the serious complications and the clinical importance of OCI in HD patients, sensitive diagnostic methods for identifying HCV RNA in the PBMCs should be implemented for all HD patients.